A Facile Synthesis of La2O3/GO Nanocomposites in N, N-Dimethylformamide with High Dye Degradation Efficiency. (26th March 2018) - He, Yong Wu; Yin, Yao Bing; Chang, Tao; Bian, Li; Zhang, Guang Qing; Li, Xiao Liang
Abstract : La2 O3 /graphene oxide (GO) nanocomposites were simply synthesized from commercially available LaCl3 ·7H2 O and multilayer GO (5–10 layers) in N, N-dimethylformamide (DMF) under reflux condition without extra stabilizer. The characterization results of scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectrum (XPS) spectroscopies showed that the crystalline La2 O3 nanoparticles were successfully attached on the surface of GO. Moreover, the as-prepared nanocomposites greatly enhanced the degradation efficiency of organic dyes after 15 min under ultrasound irradiation in pure water. The degradation efficiency of the nanocomposites for methylene blue could be over 99%.